Evaluation of fatty liver with grey scale 2D ultrasonography and ultrasound elastography and co-relation with lipid profile in adult patient in the state of Chhattisgarh attending Dr. Bhim Rao Ambedkar memorial hospital tertiary care centre Raipur - Chaudhari, Ashwini Narayan (International Surgery Journal, 2023)
Background: Several noninvasive imaging techniques have been introduced for the assessment of liver fibrosis. Among these techniques real-time Point shear wave elastography has become a promising imaging modality for the measurement of liver stiffness. The advantage of this technique is that the elasticity displayed using a B-mode image, also a quantitative estimation of liver stiffness is performed. The present study evaluates the fatty liver in patients above 18 years age with grey scale 2D ultrasonography and ultrasound elastography and also study the correlation with lipid profile in patients attending Dr B.R.A.M hospital tertiary care center Raipur, Chhattisgarh. Methods: This was a hospital based observational study conducted in Department of Radio-diagnosis, Dr BRAM Hospital and Pt JNM Medical College, Raipur (C.G). A sample of 198 patient above 18-year age with fatty liver were taken. Grading and quantification of fatty liver was also done by Shear wave elastography. A p-value <0.05 was considered statistically significant. Results: Mean age of study subjects was 48.47±15.21 years and 52.02% were female. 2D ultrasound technique diagnosed 75.25% grade-1 and 24.24% were in grade-II. Elastography technique diagnosed 57.58% with dysfunction (F1) liver stiffness, 28.28% fibrosis present (F2 or F3) and 13.64% normal. Increasing liver stiffness stages was significantly associated with increasing levels of serum VLDL (p=0.04). Conclusions: Ultrasound used in conjunction with elastography has shown utility in diagnosing and follow up of fatty liver patients. Liver stiffness was significantly associated with increasing levels of serum VLDL.